Cloning of scFv from hybridomas using a rational strategy: Application as a receptor to sensitive detection microcystin-LR in water. (October 2016) - Zhang, Xiuyuan; He, Kuo; Zhao, Ruiping; Wang, Lixia; Jin, Yandan
Abstract: Single chain variable fragment (scFv), containing of heavy and light chains (VH and VL) joined by a short peptide linker, has been used widely for immunodetection. Nevertheless, cloning functional variable genes is still a bottle neck for the scFv generation technology. Here, a rational strategy for cloning and selecting variable region genes from an anti-microcystin-LR hybridoma was devised, then the functional VH and VL genes were recloned and assembled to scFv using splicing overlap extension PCR. The resulting scFv gene was recombinantly expressed as a soluble scFv-alkaline phosphatase fusion protein (scFv−AP) by vector PLIP6/GN. Then an indirect competitive chemiluminescent enzyme immunoassay (ic-CLEIA) for detection of microcystin-LR was developed. The half-maximum inhibition concentrations (IC50 ) and limits of detection (LODs, IC15 ) were 0.81 ± 0.04 μgL −1 and 0.13 ± 0.03 μgL −1, respectively. With the mean coefficient of variation lowing 8%, the mean recovery in intra-assay and inter-assay were 100.06% and 96.46%, The proposed strategy should be useful for generation scFv in a rapid and simple way. Graphical abstract: Highlights: The functional VH and VL genes were obtained using orbitrap mass spectrometry. A high affinity anti-microcystin-LR scFv was successfully prepared. Ic-CLEIA method for detection microcystin-LR was developed.